Skrining Fitokimia, Analisis GC-MS, dan Aktivitas Antioksidan (Metode DPPH) Ekstrak Etanol Daun Sirih Cina (Peperomia Pellucida (L.) Kunth) - Putri Nurjannah; Rahma Yulia; Syarifah Nadia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Peperomia pellucida (L.) Kunth, commonly known as Chinese betel leaf, is a medicinal plant widely used in traditional medicine for various ailments. The plant is reported to contain diverse secondary metabolites with potential pharmacological activities, including antioxidant properties. However, comprehensive information on its phytochemical constituents and antioxidant potential remains limited, particularly for extracts of Indonesian origin. Objective: This study aimed to determine the phytochemical profile, chemical constituents, and antioxidant activity of the ethanol extract of P. pellucida leaves. Methods: Dried leaf powder (100 g) was extracted by maceration using 96% ethanol (1:10 w/v) for 3 × 24 hours at room temperature. Phytochemical screening was conducted using standard qualitative tests for alkaloids, flavonoids, glycosides, saponins, steroids/terpenoids, and tannins. Chemical composition was analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical-scavenging assay, with IC₅₀ values determined by linear regression analysis. Vitamin C served as the positive control. Results: The extraction yielded a concentrated ethanol extract of 11.8% (w/w). Phytochemical screening revealed the presence of flavonoids, glycosides, saponins, and terpenoids/steroids, while alkaloids and tannins were not detected. GC-MS analysis identified 14 chromatographic peaks, with major compounds including methyl hexadecanoate (14.12%), methyl 9-octadecenoate (13.61%), and triacontanoic acid. The ethanol extract exhibited very strong antioxidant activity with an IC₅₀ value of 41.47 µg/mL, compared to vitamin C (IC₅₀ = 4.083 µg/mL). The linear regression equation for the extract was y = 0.4291x + 32.2016 (R² = 0.9985). Conclusion: The ethanol extract of P. pellucida leaves contains various secondary metabolites and demonstrates very strong antioxidant activity. Although GC-MS analysis was predominantly characterized by fatty acid esters, the observed bioactivity likely results from synergistic contributions of multiple bioactive constituents. Further studies employing LC-MS/MS are recommended to identify specific compounds responsible for the antioxidant activity and to quantitatively determine total phenolic and flavonoid contents to establish their correlation with the observed bioactivity.